2023
DOI: 10.1093/eurheartj/ehad379
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 2, hyaluronan, and neutrophils play a key role in plaque erosion: the OPTICO–ACS study

Abstract: Background and aims In one-third of patients with acute coronary syndrome (ACS), thrombosis occurs despite an intact fibrous cap (IFC) (IFC–ACS, ‘plaque erosion’). Recent studies emphasize neutrophils as the immediate inflammatory response in this pathology, but their exact molecular activation patterns are still poorly understood and may represent future therapeutic targets. Methods and results Thirty-two patients with IFC–A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Collectively, these findings indicate an important role for platelets in plaque erosion, where hyaluronan is present at the plaque-thrombus interface and few leukocytes infiltrate the vascular wall [9,10,31]. Recent evidence has also demonstrated that increased HYAL-2 in thrombi found on eroded lesions occurs concomitantly with increased local levels of TLR2 ligand hyaluronic acid [131]. Neutrophil expression of TLR2 from patients with eroded plaques was also shown to be elevated compared to patients with ruptured plaques, with enhanced MMP-9 release from neutrophils and endothelial cytotoxicity [131].…”
Section: Hyaluronanmentioning
confidence: 87%
See 1 more Smart Citation
“…Collectively, these findings indicate an important role for platelets in plaque erosion, where hyaluronan is present at the plaque-thrombus interface and few leukocytes infiltrate the vascular wall [9,10,31]. Recent evidence has also demonstrated that increased HYAL-2 in thrombi found on eroded lesions occurs concomitantly with increased local levels of TLR2 ligand hyaluronic acid [131]. Neutrophil expression of TLR2 from patients with eroded plaques was also shown to be elevated compared to patients with ruptured plaques, with enhanced MMP-9 release from neutrophils and endothelial cytotoxicity [131].…”
Section: Hyaluronanmentioning
confidence: 87%
“…Recent evidence has also demonstrated that increased HYAL-2 in thrombi found on eroded lesions occurs concomitantly with increased local levels of TLR2 ligand hyaluronic acid [131]. Neutrophil expression of TLR2 from patients with eroded plaques was also shown to be elevated compared to patients with ruptured plaques, with enhanced MMP-9 release from neutrophils and endothelial cytotoxicity [131]. Data from this study provides the first in-human evidence that hyalaronic acid may promote endothelial dissociation in plaque erosion through the TLR2 neutrophil axis.…”
Section: Hyaluronanmentioning
confidence: 99%
“…Anticoagulation focuses on the prevention of thromboembolic events [1]. However, activated platelets facilitate acute arterial thrombotic events (e.g., AMI) and release pro-fibrotic and pro-inflammatory mediators [24][25][26]. Therefore, we studied the biomarkers of primary hemostasis during FDAF.…”
Section: Plasma Biomarkers Suggest Increased Platelet Activation and ...mentioning
confidence: 99%
“…A recently proposed prevailing theory regarding PE suggests that it involves multiple hits, including distinct activation of neutrophils dependent on toll-like receptor-2 (TLR2) [ 43 ]. This activation is believed to be sustained by an increased local expression of hyaluronidase 2, leading to heightened cleavage of hyaluronic acid at the coronary culprit eroded lesion [ 43 ].…”
Section: Molecular Mechanisms Of Pementioning
confidence: 99%
“…A recently proposed prevailing theory regarding PE suggests that it involves multiple hits, including distinct activation of neutrophils dependent on toll-like receptor-2 (TLR2) [ 43 ]. This activation is believed to be sustained by an increased local expression of hyaluronidase 2, leading to heightened cleavage of hyaluronic acid at the coronary culprit eroded lesion [ 43 ]. Consequently, this results in the intensified release of active MMP9 by neutrophils, exacerbating the detachment of luminal endothelial cells under disturbed flow conditions [ 43 ].…”
Section: Molecular Mechanisms Of Pementioning
confidence: 99%